Hyaluronic acid gel-core liposomes (hyaluosomes) enhance skin permeation of ketoprofen. (14th September 2019) - Kawar, Dana; Abdelkader, Hamdy
Abstract: Since FDA approval of the first transdermal patch in 1979, the utilizing of skin as a route of systemic drug administration has attracted the attention of the formulation scientists. The liposomes research in the area of transdermal drug delivery has been around for decades. This study aimed at comparing the latest gel-core liposomes (hyaluosomes) with nonconventional liposomal systems such as propylene glycol (PG)-liposomes, ethosomes, transferosomes and conventional liposomes loaded with ketoprofen. The modified thin-film hydration method was used to prepare these liposomal systems; size, zeta potential, EE%, TEM, rheological properties, in vitro release and ex vivo permeation studies were performed. Vesicle size and PDI ranged from 160 nm to 700 nm and 0.15 to 0.5, respectively. More interestingly, thermal gelation and shear-thinning characteristics were only recorded with hyaluosomes; while Newtonian behavior and low viscosity values (2 mPas.s to 6 mPa.s) were shown with all other liposomal systems. Hyaluosomes recorded superior (3-fold increases) transdermal permeation characteristics (flux and permeability coefficient), compared with other liposomal systems. With the advancement in liposomal sciences, this study warrants hyaluosomes as a promising transdermal liposomal system for favorable rheological characteristics as well as superior transdermal permeation that proved greater capacity than conventional and other non-conventional liposomal systems.